2018
DOI: 10.3906/mat-1710-46
|View full text |Cite
|
Sign up to set email alerts
|

A new proof of a Harnack inequality for the curve shortening flow

Abstract: We offer an algorithmic approach for determining Harnack quantities for the curve shortening flow and we show how, following this procedure, one can obtain Hamilton's Harnack inequality for this flow κ t + 1 2t κ ≥ κ 2 s κ , where κ is the curvature of the curve being deformed by the flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The method both determines the Harnack quantity and proves that it's non-negative, using the maximum principle. The method has proven to be able to recover classical results for other non-linear parabolic equation (see [6,7]) or for the curve shortening flow ( [4]). The procedure has its roots in the study of Ricci flow, but recently its efficiency has been observed for other heat-type equations also (see, for example, [7] for a non-linear heat equation, or [6] for the Endangered Species Equation).…”
Section: Introductionmentioning
confidence: 99%
“…The method both determines the Harnack quantity and proves that it's non-negative, using the maximum principle. The method has proven to be able to recover classical results for other non-linear parabolic equation (see [6,7]) or for the curve shortening flow ( [4]). The procedure has its roots in the study of Ricci flow, but recently its efficiency has been observed for other heat-type equations also (see, for example, [7] for a non-linear heat equation, or [6] for the Endangered Species Equation).…”
Section: Introductionmentioning
confidence: 99%